Marketing analysed of Kampung Chicken on the Traditional Market of Binjai City - J B Sitanggang; A H Daulay; T H Wahyuni; I Sembiring; M Tafsin (Jurnal Peternakan Integratif, 2019)
This study aims to identify the characteristics of farmers, agents and retailers ofkampung chicken marketing, and kampung chicken marketing channels, marketing margins,farmer share, profit ratio, and cost of kampung chicken, as well as analysed the marketingefficiency of kampung chicken in Binjai City. This research was conducted in June 2018 -August 2018. The method used in data collection by using the Jenuh sampling (sensus), whilethe sample of breeders and other marketing institutions with search method. Data collection wascarried out using interview questionnaire techniques.Data analysis included marketing costs, marketing margins, farmer share and cost benefit ratioof each marketing channel. The results of this study indicate that there are two marketingchannels. The marketing margin on channel II shows margin Rp. 15.157,-. the farmer’s inchannel I 76.19% and ratio of profit Rp. 2.4 per kg on channel II. The marketing channel forkampung chicken in the Traditional Market of Binjai City is efficient.